Dialogical "mechanisms" of formation of cultural identity - Darenskyi, Vitalii (Actual Problems of Mind, 2017)
The article raises questions of history and the heuristic sense of the concept of "identity", as well as the specifics of dialogical relations as the process of identity formation.